PENGARUH PENDIDIKAN DAN PENGALAMAN KERJA MELALUI MOTIVASI TERHADAP KINERJA KARYAWAN RUMAH SAKIT PERTAMINA TANJUNG KABUPATEN TABALONG - Shinta Avriyanti; Indriati Sumarni; Ma'rifatus Zuhro (Jurnal PubBis, 2019)
Research is to find out and analyze 1) influence of education against Pertamina Hospital employee motivation Tanjung Tabalong Regency; 2) Influence of education on performance of employees of Pertamina Hospital Tanjung Tabalong Regency; 3) influence of work experience against Pertamina Hospital employee motivation Tanjung Tabalong Regency; 4) Influence of work experience on performance of employees of Pertamina Hospital Tanjung Tabalong Regency; 5) Influence of motivation on performance of employees of Pertamina Hospital Tanjung Tabalong Regency; 6) Influence of the education, work experience, motivation on performance of employees of Pertamina Hospital Tanjung Tabalong Regency; 7) to know the influence of the education, work experience through motivation on performance of employees of Pertamina Hospital Tanjung Tabalong Regency. This research is eksplanatory research. The approach used in this study was the quantitative approach. Sampling method with the method of probability sampling techniques in the collection of data in this study are: 1) the study of librarianship; and 2) Questionnaires or question form. Questionnaires or question form is the main instrument with 30 sample respondents from a nurse who works at the hospital of Pertamina Tanjung Tabalong Regency. Methods of data analysis using Generalized Structured Component Analysis (GSCA). The research results showed that: 1) there was no influence of Education against Pertamina Hospital employee motivation Tanjung Tabalong Regency; 2) there is the influence of Education on performance of employees of Pertamina Hospital Tanjung Tabalong Regency; 3) there is no working experience influence employee motivation against Pertamina Hospital Tanjung Tabalong Regency; 4) there is the influence of work experience on performance of employees of Pertamina Hospital Tanjung Tabalong Regency; 5) there was no influence of Motivation on performance of employees of Pertamina Hospital Tanjung Tabalong Regency; 6) there is the influence of the Education, work experience, motivation on performance of employees of Pertamina Hospital Tanjung Tabalong Regency; 7) there is no influence on education, work experience through Motivation on performance of employees of Pertamina Hospital Tanjung Tabalong Regency. Keywords : Education; Work Experience; Motivation; Performance.